Exposure to secondhand smoke in terraces and other outdoor areas of hospitality venues in eight European countries. - Maria J López (Public Library of Science (PLoS), 2012)
Background Outdoor secondhand smoke (SHS) concentrations are usually lower than indoor concentrations, yet some studies have shown that outdoor SHS levels could be comparable to indoor levels under specific conditions. The main objectives of this study were to assess levels of SHS exposure in terraces and other outdoor areas of hospitality venues and to evaluate their potential displacement to adjacent indoor areas. Methods Nicotine and respirable particles (PM2.5) were measured in outdoor and indoor areas of hospitality venues of 8 European countries. Hospitality venues of the study included night bars, restaurants and bars. The fieldwork was carried out between March 2009 and March 2011. Results We gathered 170 nicotine and 142 PM2.5 measurements during the study. The median indoor SHS concentration was significantly higher in venues where smoking was allowed (nicotine 3.69 µg/m3, PM2.5: 120.51 µg/m3) than in those where smoking was banned (nicotine: 0.48 µg/m3, PM2.5: 36.90 µg/m3). The median outdoor nicotine concentration was higher in places where indoor smoking was banned (1.56 µg/m3) than in venues where smoking was allowed (0.31 µg/m3). Among the different types of outdoor areas, the highest median outdoor SHS levels (nicotine: 4.23 µg/m3, PM2.5: 43.64 µg/m3) were found in the semi-closed outdoor areas of venues where indoor smoking was banned. Conclusions Banning indoor smoking seems to displace SHS exposure to adjacent outdoor areas. Furthermore, indoor settings where smoking is banned but which have a semi-closed outdoor area have higher levels of SHS than those with open outdoor areas, possibly indicating that SHS also drifts from outdoors to indoors. Current legislation restricting indoor SHS levels seems to be insufficient to protect hospitality workers--and patrons--from SHS exposure. Tobacco-free legislation should take these results into account and consider restrictions in the terraces of some hospitality venues to ensure effective protection.